Structure, genesis and resources efficiency of dolomite: new insights and remaining enigmas - Cai, Wen Kai; Liu, Jia Hui; Zhou, Chun Hui; Keeling, John; Glasmacher, Ulrich A. (Chemical geology, 2021)
Dolomite can form as a major mineral component of marlstones and limestones and is an important sink for magnesium in the marine environment. Dolomite is widely distributed in time and space and is considered an intrinsic ingredient in the evolution of the Earth’s crust. The crystal structure and genesis of dolomite record fundamental geochemical and environmental processes of significance in the Earth’s element cycle process, carbon storage, and paleoenvironments, with relevance to the exploration for minerals and fossil fuels, management and maintenance of the environment, and the use of carbonate minerals by industry. The review brings together new advances and insights from recent studies on dolomite structure, geological genesis, laboratory synthesis, and applications. In the mantle, dolomite may adapt to increasing pressure by structural rearrangement and undergoes crystal phase transitions. At present, four high-pressure polymorphs have been identified. The phase transitions allow dolomite to survive subduction into the mantle, possibly into the transition zone, but stability is not fully predictable and is influenced by factors that include initial degree of cation ordering in dolomite and Fe and Mn substitution for Mg in the dolomite crystal lattice. The presence of Fe and Mn is influenced by the environment of dolomite formation. The key factors controlling formation of dolomite, including transition or recrystallization from precursor high-Mg calcite or proto-dolomite, at low temperatures remain ambiguous. Sulfate-reducing bacteria, methanogens, and aerobic bacteria, the exudates or relevant extracellular polymeric substances, fluctuating environmental conditions, and the negatively charged surfaces of clay minerals all can mediate high-Mg calcite/proto-dolomite formation at low temperature. As for secondary dolomite, formed by Mg2+ replacement of Ca2+ in carbonate minerals, several models have been proposed and widely adopted, including: near-surface dolomitization, burial dolomitization, and hydrothermal dolomitization. The formation of massive deposits of dolomite in marine sediments probably involves multiple dolomitization processes. Yet the “dolomite problem” remains enigmatic. Mg isotope analysis, an emerging technology, offers a new approach to further investigate the genesis of dolomite. In the laboratory, synthesis of dolomite at low temperature has yet to be achieved. Fundamental scientific research on dolomite is expected to inform the sustainable use of dolomite resources. Traditional uses of dolomite typically in construction materials, refractory, and flux continue. Now, the use of dolomite and its calcined products is being expanded into environmental protection, soil improvement, thermochemical energy storage and biomedical materials.
Gesehen am 25.06.2021